KESEJAHTERAAN PSIKOLOGIS GURU HONORER DI MI SINDON 2 NGEMPLAK BOYOLALI - Banabsyah Iryanto, Jagad; Purnomosidi, Faqih; Riskiana Putri, Dhian (JURNAL TALENTA PSIKOLOGI, 2023)
Honorary teachers have the right to receive an honorarium monthly and quarterly based on government regulations in labor law (Mulyasa, 2016). Honorary teachers in the regions should feel the increase in psychological well-being. It is due to honorary teachers have served for a very long time with minimum wages.The research aims to describe how the psychological well-being of honorary teachers at MI Sindon 2 Ngemplak Boyolali used a qualitative approach. Observation and interview methods are arranged based on aspects of psychological well-being according to Ryff and Keys.The results show that honorary teachers at MI Sindon 2 Ngemplak Boyolali have good psychological well-being and the wages do not affect their psychological well-being.